Contribution of Experimental Animal Research Studies to the Emergency Medicine Literature - Umut Ocak; John H. Zhang (Emergency Medicine International)
The aim of this study is to provide a detailed analysis of emergency medicine (EM) research literature to unveil the trends while underlining the importance of experimental research for all territories of science. To this end, the experimental animal research articles published in EM journals indexed to the Science Citation Index Expanded database with a date of publication between January 1, 2008, and December 31, 2017, were reviewed retrospectively. All data regarding the journal name, publication year, country, department and institution of the first author, subject species, type of the experimental model, target organ/system/functions, evaluation method, outcome measures, and citation counts were noted. Resultantly, a total of 736 articles were found to be published in 18 journals. Resuscitation (n=285, 38.7%) had the highest number of articles followed by Injury (n=143, 19.4%), Turkish Journal of Trauma and Emergency Surgery (n=128, 17.4%), and American Journal of Emergency Medicine (n=63, 8.6%). The USA was the largest contributor with 199 studies (27%). The department of the first author was EM in 190 (28.8%) of the reports. Various versions of cardiac arrest models were applied in 257 (34.9%) studies while brain (n=101, 13.7%) was the most commonly explored area. The main outcome measures were clinical outcomes/survival rates (n=408, 55.43%). The molecular mechanisms of the injury were evaluated in 37 (5%) of the studies. In conclusion, experimental animal studies are essential in the progress of contemporary scientific knowledge. EM journals should encourage and consider giving more place to experimental research given their undisputed worth and potential future contributions to science, including the field of EM.